Numerical study on optimization of quantitative treatment conditions for skin cancer photothermal therapy considering multiple blood vessels - Kim, Donghyuk; Kim, Hyunjung (Computer Methods and Programs in Biomedicine, 2023)
Background: In recent years, lasers have gained considerable attention as a potential treatment option in the medical field. Photothermal therapy, in particular, has been investigated as a technique to remove tumor tissue by leveraging photothermal effects. The method involves raising the temperature of the tumor tissue to destroy it and has primarily been studied for skin cancer treatment. Objective: This study aimed to simulate a skin layer with squamous cell carcinoma by using numerical modeling and investigate the effect of different numbers of blood vessels on the temperature distribution in the medium under conditions such as varied laser intensity and gold nanoparticle volume fraction. Methods: Optical properties of the light absorption enhancer were calculated using the discrete dipole approximation method, and the temperature and velocity distribution were computed using continuity, momentum, and energy equations. Results: Quantitative determination of the apoptotic variable was performed to evaluate the treatment effect for each case, and the treatment condition with the maximum treatment effect was identified. Laser intensity with optimal therapeutic effect was confirmed to be 0.13 W, 0.15 W, 0.18 W, and 0.24 W, depending on the number of vessels, respectively, and the volume fraction of injected GNRs was confirmed to be 10−6 for all vessel numbers. Conclusion: The results of this study can serve as a guide for selecting appropriate treatment conditions when conducting photothermal therapy in the future
Keywords: Gold nanoparticle; Gold Nanoparticles; Laser intensities; Optimisations; Photothermal therapy; Skin cancers; Thermal damage; Treatment conditions; Treatment effects; Tumour tissue; Carcinoma, Squamous Cell; Gold; Humans; Metal Nanoparticles; Photothermal Therapy; Skin Neoplasms; Apoptosis; Blood vessels; Gold nanoparticles; Photothermal therapy; Thermal damage